Ephemeral Secrets: Multi-Party Secret Key Acquisition for Secure IEEE 802.11 Mobile Ad Hoc Communication - David Samuel Bhatti; Shahzad Saleem (IEEE Access, 2020)
Mobile ad hoc networks consist of wireless nodes and can be established quickly with minimal configuration and cost, because, they do not require any infrastructure in advance. Civil and military applications are using them extensively in emergency and mission-oriented scenarios respectively as multi-party communication systems. Whereas, the multi-party secret key acquisition is one of the acute issues in these low resource wireless ad hoc networks, especially, which are based on IEEE 802.11ah and IEEE 802.11ba (low power WiFi), IEEE 802.15.4(Zigbee), BLE, IEEE 802.15.6 (body-worn or wearable) devices. In this study, a novel low cost and robust approach has been proposed and tested to establish an identical secret key in a multi-user mobile ad hoc environment. We believe, it is one of the groundbreaking contributions toward establishing a cost-effective secret key acquisition solution with respect to memory, computation, and bandwidth. We have used Bloom-Filters to cope with these resource limitations of such wireless setups. The proposed approach has been tested using IEEE 802.11 adapters in a real environment, and we found it to be highly suitable for wireless resource-limited applications.